A successful new method for single left lobe recruitment. Issue 12 (18th October 2018) - Dybwik, Knut; Nielsen, Erik W.
Key Clinical Message: Any gas will flow down the path of least resistance and highest compliance. This is a problem in the treatment of severe unilateral lung disease in the intensive care unit (ICU). Deep sedation interferes with the diaphragm's ability to distribute air into the lower lung. Spontaneous breathing in a conscious patient, in combination with mechanical ventilation via an endotracheal tube inserted into the left main stem bronchus, can recruit collapsed alveoli. Abstract : Any gas will flow down the path of least resistance and highest compliance. This is a problem in the treatment of severe unilateral lung disease in the intensive care unit (ICU). Deep sedation interferes with the diaphragm's ability to distribute air into the lower lung. Spontaneous breathing in a conscious patient, in combination with mechanical ventilation via an endotracheal tube inserted into the left main stem bronchus, can recruit collapsed alveoli.